IMPLEMENTASI DIPLOMASI BUDAYA MELALUI FOTOGRAFI DAN VISUAL STORYTELLING OLEH JAKARTA INTERNATIONAL PHOTO FESTIVAL - Salsabila (2023)
This research focuses on the role of cultural diplomacy in promoting the exchange of ideas and perspectives between countries through photography and visual storytelling. Specifically, the researcher examines the implementation of cultural diplomacy through the Jakarta International Photo Festival, which has become an important platform to promote Indonesian culture. The purpose of this research is to analyze how cultural diplomacy shapes the promotion of Indonesian culture and the strengthening of cultural relations between Indonesia and the Netherlands. This research concludes that the Jakarta International Photo Festival has played an important role in promoting cultural exchange and collaboration, as well as contributing to the strengthening of intercultural diplomatic relations between the two countries.